The functional role of temperate forest understorey vegetation in a changing world. (26th August 2019) - Landuyt, Dries; De Lombaerde, Emiel; Perring, Michael P.; Hertzog, Lionel R.; Ampoorter, Evy; Maes, Sybryn L.; De Frenne, Pieter; Ma, Shiyu; Proesmans, Willem; Blondeel, Haben; Sercu, Bram K.; Wang, Bin; et al.
Abstract: Temperate forests cover 16% of the global forest area. Within these forests, the understorey is an important biodiversity reservoir that can influence ecosystem processes and functions in multiple ways. However, we still lack a thorough understanding of the relative importance of the understorey for temperate forest functioning. As a result, understoreys are often ignored during assessments of forest functioning and changes thereof under global change. We here compiled studies that quantify the relative importance of the understorey for temperate forest functioning, focussing on litter production, nutrient cycling, evapotranspiration, tree regeneration, pollination and pathogen dynamics. We describe the mechanisms driving understorey functioning and develop a conceptual framework synthesizing possible effects of multiple global change drivers on understorey‐mediated forest ecosystem functioning. Our review illustrates that the understorey's contribution to temperate forest functioning is significant but varies depending on the ecosystem function and the environmental context, and more importantly, the characteristics of the overstorey. To predict changes in understorey functioning and its relative importance for temperate forest functioning under global change, we argue that a simultaneous investigation of both overstorey and understorey functional responses to global change will be crucial. Our review shows that such studies are still very scarce, only available for a limited set of ecosystem functions and limited to quantification, providing little data to forecast functional responses to global change. Abstract : The understorey in temperate forests is an important biodiversity reservoir that can influence ecosystem functioning in multiple ways. We here compiled studies that quantify the relative importance of the understorey for temperate forest functioning, focussing on litter production, tree regeneration, nutrient cycling and evapotranspiration and show that the understorey's contribution to temperate forest functioning is significant but varies depending on the ecosystem function and the environmental context. Our review also shows that studies that quantify both overstorey and understorey functioning are still scarce, providing little data to forecast changes in the understorey's relative importance under global change.